Antimicrobial effect and microbial adherenceto maxillofacial prosthetic materials - Rahman, Farhana (2021)
Maxillofacial prostheses are used to restore the functional and anatomical defects of the maxillofacial region caused by trauma or tumour. It is beneficial to the patients if the materials used for the fabrication of the maxillofacial prostheses could demonstrate antimicrobial effects and resist microbial adherence hence reducing the risk of infection. The objective of this study is to evaluate the antimicrobial effect, surface roughness and microbial adherence of the locally produced material namely modified polymethyl methacrylate (m-PMMA) against commercially produced polymethyl methacrylate (c-PMMA), silicone A-2000 and silicone A-2186 which are commonly used materials for maxillofacial prostheses. The microbial strains namely Staphylococcus aureus (S. aureus), Streptococcus mutans (S. mutans) and Candida albicans (C. albicans) were used in this study. Antimicrobial effect of maxillofacial prosthetic materials was determined by agar diffusion test, whilst microbial adherence was analysed using a direct colony-counting method and surface roughness of tested materials was determined using profilometer. Scanning electron microscopy (SEM) images were also used to examine the surface roughness and microbial adherence. One-way ANOVA was used to analyse surface roughness and Multivariate Analysis Of Variance (MANOVA) was used to analyse microbial adherence. For antimicrobial activity, it was observed that all tested materials did not inhibit the growth of all tested microbial strains. Surface roughness analysis showed significant difference (p<0.05) between PMMA and silicone elastomers. There was also significant difference in bacterial adherence on the tested materials in which significantly higher colony-forming unit (CFU) of S. aureus and S. mutans were observed on roughened surfaces namely silicone elastomers than that of PMMA (p>0.017). No significant difference was observed in the adherence of C. albicans between silicone elastomers and PMMA. It can be concluded that the presence of fillers in m-PMMA may not be adequate to promote the release of antimicrobial agents, however, m-PMMA showed less microbial adherence in comparison to other tested materials. The findings also demonstrate that surface roughness of the materials play an important role in microbial adherence.